Analytical Modeling of Potential Distribution and Threshold Voltage of Gate Underlap DG MOSFETs with a Source/Drain Lateral Gaussian Doping Profile - Singh K.; Kumar M.; Goel E.; Singh B.; Dubey S.; Kumar S.; Jit S. (My University, 2025)
This paper reports a new two-dimensional (2D) analytical model for the potential distribution and threshold voltage of the short-channel symmetric gate underlap ultrathin DG MOSFETs with a lateral Gaussian doping profile in the source (S)/drain (D) region. The parabolic approximation and conformal mapping techniques have been explored for solving the 2D Poisson’s equation to obtain the channel potential function of the device. The effects of straggle parameter (of the lateral Gaussian doping profile in the S/D region), underlap length, gate length, channel thickness and oxide thickness on the surface potential and threshold voltage have been investigated. The loss of switching speed due to the drain-induced barrier lowering (DIBL) has also been reported. The proposed model results have been validated by comparing them with their corresponding TCAD simulation data obtained by using the commercially available 2D ATLAS™ simulation software. © 2015, The Minerals, Metals & Materials Society.